The Role of Coaches in Increasing Student Motivation Through Basketball Games in Schools (A Review of Literature Studies) - Doni Pranata; I Putu Agus Dharma Hita; Reza Resah Pratama; Rizki Hazazi Ali; Witri Suwanto; Elsa Ariestika (Universitas PGRI Palembang, 2023)
Student motivation in learning basketball can affect their academic achievement and sports performance. Coaches have an important role in increasing student motivation in school through basketball learning. However, there have not been many studies that examine the role of coaches in increasing student motivation through basketball games at school. The purpose of this study is to explain the role of coaches in increasing student motivation through basketball games at school, as well as to find out what methods and strategies can be used by coaches in increasing student motivation. This research uses a literature study approach by searching various databases and information sources, such as scientific journals, books, and online articles. The data obtained is then analyzed and compiled into a synthesis. The results of this study show that the role of coaches in increasing student motivation through basketball games in schools is very important. Coaches must be able to build good relationships with students, provide positive feedback, and provide challenges that match students' ability to increase their confidence and motivation. Based on the results and discussion of this study, it is suggested that basketball coaches in schools should pay more attention to their role in increasing student motivation. The coach must master various effective methods and strategies to increase student motivation in learning and playing basketball. Trainers should also pay attention to the balance between theory and practice, as well as adopt the latest technologies and innovations to increase student learning and motivation.